Evaluating some haemostatic profiles and platelet aggregation in gestational diabetes mellitus subjects - Atere, A.D.; Kosamat, Y.A.; Adeyemi, O.A.; Zubairu, S.O.; Akanni, O.E. (Research journal of health sciences, 2023)
Background: Hypercoagulability has been linked to an increase in risk factors, making diabetes a major cause of morbidity and mortality in low-income countries like Nigeria. This research examined some haemostatic parameters in women with gestational diabetes mellitus (GDM).Methodology: A total of 100 subjects consisting of 40 GDM, 30 non-gestational diabetes pregnant women (NGPW) attending the ante-natal clinic of the hospital and 30 women with neither diabetes nor pregnancy (NDNP) were enrolled as controls in this study. Ten milliliters of blood was collected and dispensed into an appropriate anticoagulant bottle. Prothrombin time (PT), Activated partial Thromboplastin Time (APTT), complete blood count (CBC) and fasting blood sugar (FBS) was estimated using standard techniques.Results: There was a significantly higher in the mean values of FBS, PT, APTT and WBC among GDM and NGPW when compared with NPNP (p<0.05), while PCV was lower. FBS has positive correlation with PT and APTT while it shows negative correlation with platelet. APTT had a little edge over PT with higher area under the ROC curve of 0.997 than PT among GDM.Conclusion: In this study, women with GDM have considerably longer PT and APTT than NGPW and NDNP. Therefore, there may be possibility of haemorrhagic complications in gestational diabetes.